Meneroka faktor resilien dalam kalangan remaja hamil tanpa nikah yang tinggal di pusat perlindungan - Noraffy Ahmad,; Nasrudin Subhi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The phenomenon of unwed teenage mothers across the world including in Malaysia is alarming. Therefore, the Malaysian Government had taken a few measures in order to curb this problem. However, statistics shows that teenage pregnancy and baby dumping cases were still increasing. This research was conducted to explore factors influencing resilience among unwed teenage mothers living in a shelter home. This qualitative study using in depth interviews as means in collecting data. A total number of five teenage mothers living in a shelter home were chosen as informants in the current study using purposive sampling technique. Analysis of the data was conducted using thematic analysis where patterns of theme found were grouped together in order to form a final theme. The study revealed that there are three major factors that affect resilience adaptation among the informants. The factors include family processes, community processes, and individual attributes. These factors could serve as either risk factors or protective factors depending on their impact towards the informants. Thus, it is suggested that the management of shelter homes collaborate with professionals such as psychologists and social workers in developing a holistic module which comprised all three resilience factors in order to reduce the probability of relapsed among ex-residence of shelter homes. In the meantime, suggestions for future research were also provided.